Problem-Based Entrepreneurship Learning: The Role of Self-Efficacy Moderation in Strengthening Students’ Creative Thinking - Iyan Setiawan; Herlina; Moh. Imron Rosidi (CV. Creative Tugu Pena, 2026)
The low level of creative thinking skills among students is one of the main challenges in entrepreneurship education in higher education. The learning pattern, which is still dominated by a one-way approach, means that students have little opportunity to discuss, develop ideas, and express creative ideas. This situation calls for learning strategies that can actively and reflectively stimulate creative thinking skills. This study aims to analyse the effectiveness of the Problem-Based Learning (PBL) model on students' creative thinking skills in entrepreneurship courses, considering the role of self-efficacy as a moderating variable. The research used a quasi-experimental approach with a pretest-posttest factorial design, involving seventh semester A students as the experimental class and seventh semester B students as the control class in the odd semester of the 2024-2025 academic year in the Law Study Programme at Kuningan University. Data were collected through creative thinking tests and self-efficacy questionnaires, then analysed using a two-way ANOVA test to examine the main effects of the interaction between variables. The results showed that: (1) students who learned using the Problem-Based Learning model had higher levels of creative thinking compared to those who learned using the lecture method; (2) self-efficacy had a significant effect on students' abilities; and (3) there was a meaningful interaction between the Problem-Based Learning model and self-efficacy, as indicated by greater increases in creativity through the application of Problem-Based Learning. These findings confirm that the integration of Problem-Based Learning with the strengthening of self-efficacy is an effective strategy in learning. In addition, this study can contribute theoretically to the development of a constructivist-based entrepreneurial learning model in which students successfully solve problems contextually.